Comparative Analysis of Diagnostic Accuracy in Retinal Imaging: Fundus Photography Versus Optical Coherence Tomography - Carretero, Manuel Moriche; Parejo, Ana de los Reyes Sánchez; Pérez, Clara Martínez; Amores, Remedios Revilla; Gómez, Ángel Pérez; Pérez, Marc Biarnés (Science and Technology: Developments and Applications Vol. 2, 2025)
Background: According to the World Health Organization, globally, at least 2.2 billion people have a vision impairment or blindness, of whom at least 1 billion have a vision impairment that could have been prevented or has yet to be addressed. This study aimed to determine the diagnostic accuracy that optical coherence tomography (OCT) can add to fundus photography (FP) in assessing the condition of the retinal posterior pole. Methods: We conducted two blocks of analysis: First, the posterior pole of each eye was examined using an FP non-mydriatic imaging device. Second, OCT was used in addition to FP. After consolidating the specific diagnostic criteria, the assessments were evaluated using two blinded independent investigation groups (by optometrists, and by ophthalmologists who were considered the gold standard). Each research investigation group graded the posterior pole of each eye based on the same information provided in the two assessment blocks. Results: The sample consisted of 1334 eyes from 667 people. We calculated the diagnostic accuracy of FP compared to OCT and found that they had similar sensitivity. FP had a slightly higher specificity (p-value: 0.01), and OCT had a higher kappa coefficient with 0.50 (95% CI: 0.46–0.55) vs. 0.39 (95% CI: 0.34–0.45) for FP. Conclusions: On the basis that the role of the optometrist in Spain is not to diagnose but to detect lesions and refer patients to an ophthalmologist, the results of this study support the use of OCT, which provided gradable images in almost all examined eyes (97.5%, 1301 eyes) compared to FP (73.5%, 980 eyes). However, optometrists need a detailed and standardized guide in order to conduct evaluations according to the ophthalmologist’s criteria. The addition of OCT to a screening modality with FP could resolve the issue that 1 in 10 eyes with visible abnormalities on OCT images are not identified by the ophthalmologists when the assessment is based on FP alone.